TEACHER’S STRATEGIES IN BUILDING THE STUDENTS’ KNOWLEDGE OF THE FIELD (BKOF) IN TEACHING WRITING NARRATIVE TEXT - Astrina Nur Sundari; Nenden Sri Lengkanawati; Nicke Yunita Moecharam (Journal of English and Education, 2017)
This study is aimed at investigating the teacher’s strategies at the stage of building knowledge of the field (BKOF) especially when teaching writing narrative text. The BKOF stage is intended to build the students’ prior knowledge before they can write effectively. This study used the scaffolding theory as it shares some similarities with the BKOF stage. Qualitative research was applied in this study. Four instruments were used to collect the data; questionnaire, classroom observation, interview and document analysis. The findings showed that the teacher applied three main strategies in the BKOF stage, those are 1) asked students to translate in most of the class discussion; 2) built students vocabulary; and 3) the point system.